HyTan chestnut tannin: an effective biostimulant for the nursery production of high-quality grapevine planting material - Pisciotta, Antonino; Ciriminna, Rosaria; Planeta, Diego; Miccichè, Daniele; Barone, Ettore; Di Lorenzo, Rosario; Puccio, Stefano; Turano, Lucia; Scurria, Antonino; Albanese, Lorenzo; Meneguzzo, Francesco; Pagliaro, Mario (Frontiers in Agronomy, 2025)
IntroductionHyTan, a new chestnut tannin extracted from chestnut wood via hydrodynamic cavitation at low temperature in water only, is an effective biostimulant for the nursery production of high-quality grapevine planting material.MethodsExperiments were carried out in Sicily with HyTan aqueous extracts obtained at different temperatures (45, 60 and 75°C) and dosage (pure extract or diluted with water) on the above-ground and below-ground characteristics of cv. Zibibbo cuttings grafted on rootstock 1103 Paulsen.Results and discussionHyTan tannin extracted at low temperature (45°C) favored the growth of both thinner root fraction and total above-ground plant as well as the leaf chlorophyll content. These findings open the route to the widespread use in agriculture of this newly extracted chestnut tannin rich in ellagic acid, nonhydrolyzed ellagitannins (castalagin and vescalagin) and gallic acid.